Bio-based compatible stable particle as well as preparation method and application thereof

By using heat-triggered bio-based crosslinking agent and bio-based nanocomposite in high viscosity asphalt, the compatibility problem between high content of SBS and asphalt is solved, the stability and performance of the material are improved, and environmental pollution is reduced and production costs, achieving environmental protection and economical modification paths.

CN119463468AActive Publication Date: 2025-02-18BEIJING UNIV OF TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411687549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the prior art, the compatibility problem between high content SBS and asphalt causes the high viscose asphalt system to be thermodynamic incompatible, prone to stratification and phase separation, affecting its performance and stability. At the same time, commonly used chemical additives such as sulfur and polyphosphoric acid have potential adverse effects on the environment, and the preparation process is complex, which increases production costs and technical thresholds.

Method used

The thermally triggered bio-based crosslinking agent and bio-based nanocomposite are used to improve the compatibility stability, durability and high-temperature rheology performance of high viscosalt asphalt through chemical crosslinking and enhancement of nanocomposite materials. Thermal triggered bio-based crosslinking agent is activated at high temperatures and participates in the chemical modification of high viscose asphalt. Bio-based nanocomposites improve the internal molecular structure and interface bonding properties of asphalt.

Benefits of technology

It has achieved the compatibility stability and overall performance improvement of high viscosal asphalt, reduced environmental pollution, simplified the preparation process, reduced production costs, and conformed to modern environmental protection concepts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463468A_ABST
    Figure CN119463468A_ABST
Patent Text Reader

Abstract

The invention discloses a bio-based compatible stable particle and a preparation method and application thereof, and belongs to the technical field of road asphalt material preparation, the bio-based compatible stable particle comprises the following raw materials: a thermal trigger type bio-based cross-linking agent, a bio-based nano composite material, a tackifier, a titanate coupling agent and an antioxidant. The thermal triggering type bio-based cross-linking agent and the bio-based nano composite material are used for replacing cross-linking agents such as sulfur and polyphosphoric acid which are commonly used in the prior art and are prepared into the bio-based compatible stable particles which can be directly put into use, and the method has the advantages of being obvious in material stability and convenient to construct. The application of the bio-based material can effectively reduce the emission of harmful gases in the production and application process of the high-viscosity asphalt and improve the construction environment. Meanwhile, the biodegradation characteristic of the bio-based material provides powerful support for environmental protection, and the long-term pollution risk after the material is used is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road asphalt material preparation, and in particular relates to a bio-based compatible stable particle and a preparation method and application thereof. Background Art

[0002] With the continuous development of road material engineering, the demand for high-performance road materials is increasing. Polystyrene-block polybutadiene-polystyrene (SBS) has become a popular choice for improving asphalt performance due to its excellent elasticity and resilience. However, although SBS has shown good performance in modified asphalt, its application still has some significant limitations. Among them, the compatibility problem between high-content SBS and asphalt is particularly prominent in modification research. The differences in physical and chemical properties between SBS and asphalt lead to their thermodynamic incompatibility, and the high-viscosity asphalt system formed is prone to stratification and phase separation, which not only reduces the performance of high-viscosity asphalt, but also significantly affects its stability during construction and service.

[0003] Patent CN102977619A uses acidifying accelerator M, waste residue, sulfur, accelerator and resin as raw materials to compound a polymer for the stability of modified asphalt, and waste residue can be used to promote vulcanization to solve the problem of waste residue treatment. Patent CN118185328A adds sulfur and light oil to SBS asphalt to promote the chemical grafting reaction and solubility of SBS and asphalt, and is supplemented with substances such as vulcanization accelerators and dispersants to improve the development and uniformity of the cross-linked network structure. These methods can improve the compatibility stability problem of high-viscosity asphalt to a certain extent, but the potential adverse effects of chemical additives such as sulfur and polyphosphoric acid on the environment cannot be ignored, especially in the context of the current global advocacy of green buildings and environmental protection concepts, this problem is particularly important. In addition, these disclosed methods often include complex preparation processes, which not only increase production costs, but also bring challenges to the operability of process implementation and the convenience of on-site construction. For many practical applications, simplifying the modification process and lowering the technical threshold are the keys to improving the efficiency of material application. Therefore, while seeking to improve compatibility and stability, we must also take into account environmental protection and economy and open up a green and simple modification path. Summary of the invention

[0004] The purpose of the present invention is to provide a bio-based compatible stable particle and its preparation method and application to solve the problems existing in the above-mentioned prior art. The present invention uses a heat-triggered bio-based cross-linking agent as a cross-linking agent to increase the chemical cross-linking degree between high-parameter SBS and asphalt, and enhances the mechanical properties and rheological properties of high-viscosity asphalt through a bio-based nanocomposite material, thereby obtaining an environmentally friendly and usable high-viscosity asphalt material.

[0005] One of the technical solutions:

[0006] The invention discloses bio-based compatible stable particles, the raw materials of which include a heat-triggered bio-based cross-linking agent, a bio-based nano-composite material, a tackifier, a titanate coupling agent and an antioxidant.

[0007] Preferably, the mass ratio of the heat-triggered bio-based cross-linking agent, the bio-based nanocomposite material, the tackifier, the titanate coupling agent and the antioxidant is (3-5):(3-6):(3-5):(2-4):1.

[0008] Preferably, the raw materials of the heat-triggered bio-based cross-linking agent include a polyisocyanate compound, a bio-based polyol, dibutyltin dilaurate and a solid blocking agent; wherein the polyisocyanate compound is selected from 4,4'-diphenylmethane diisocyanate or isophorone diisocyanate; the bio-based polyol is selected from epoxy castor oil, epoxy soybean oil or epoxy linseed oil; and the solid blocking agent is selected from 3,5-dimethylpyrazole DMP, dimethylglyoxime or sodium bisulfite.

[0009] Preferably, the preparation method of the heat-triggered bio-based cross-linking agent comprises the following steps: under a nitrogen atmosphere, adding the dibutyltin dilaurate to a mixture of the polyisocyanate compound and the bio-based polyol, heating and stirring to react, then adding a solution containing a solid blocking agent, continuing to stir the reaction, and vacuum drying the reaction product to obtain the heat-triggered bio-based cross-linking agent.

[0010] More preferably, the temperature of the heating and stirring reaction is 50-80°C; the temperature of the continued stirring reaction is 50-80°C and the time is 3 hours; the temperature of the vacuum drying is 80°C and the time is 2 hours; the solvent in the solution containing the solid sealing agent is selected from N,N-dimethylacetamide or N,N-dimethylsulfamide.

[0011] More preferably, the ratio of -NCO groups in the polyisocyanate compound, -OH groups in the bio-based polyol and -OH groups in the solid blocking agent is 1:(0.25-0.5):(0.6-0.9).

[0012] The above group ratio is limited in order to obtain a prepolymer with terminal isocyanate groups and ensure that its reaction activity can be completely protected by the solid blocking agent, thereby obtaining a heat-triggered bio-based cross-linking agent with stable performance.

[0013] The present invention adopts a heat-triggered bio-based cross-linking agent to comprehensively improve the compatibility stability, durability and high-temperature rheological properties of high-viscosity asphalt; on the one hand, the use of bio-based materials significantly reduces environmental pollution and improves sustainability, which is in line with modern environmental protection concepts. On the other hand, the solid closed form effectively protects the reactivity of the terminal -NCO of the bio-based cross-linking agent, so that it can be prepared into solid particles, which is convenient for practical operation and storage. The heat-triggered bio-based cross-linking agent is a bio-based cross-linking agent with high reactivity that can be generated under high-temperature triggering of 160-190°C. The preparation of high-viscosity asphalt generally requires high temperature to ensure that the high-content polymer and asphalt are fully miscible. Under this condition, the heat-triggered bio-based cross-linking agent is added to the high-viscosity asphalt to successfully trigger its reactivity, thereby chemically cross-linking with the two-phase components (SBS phase and asphalt phase) in the high-viscosity asphalt.

[0014] The heat-triggered bio-based cross-linking agent provided by the present invention is a non-toxic and stable solid powder, which can generate a bio-based cross-linking agent with high reactivity under high temperature triggering of 160-190°C. The terminal -NCO group of the bio-based cross-linking agent can actively participate in the chemical modification of high-viscosity asphalt, thereby achieving the enhancement of the performance of high-viscosity asphalt.

[0015] Preferably, the raw materials of the bio-based nanocomposite material include nanofillers, bio-based organic acids and catalysts, wherein the nanofillers are selected from nano OvPOSS, nano calcium carbonate or nano silicon dioxide; the bio-based organic acids are selected from oleic acid, stearic acid, palmitic acid or linoleic acid; and the catalysts are selected from triethylaminosilane, coupling agent A185 or sodium hydroxide.

[0016] Preferably, the method for preparing the bio-based nanocomposite material comprises the following steps: adding the nanofiller to an organic solvent, mixing and preheating, then adding the bio-based organic acid and catalyst, stirring for reaction, filtering, washing, and vacuum drying to prepare the bio-based nanocomposite material.

[0017] More preferably, the preheating temperature is 90-100°C; the stirring reaction time is 2 hours; the washing is washing the filtrate with ethanol and distilled water in sequence; the vacuum drying temperature is 80-100°C and the time is 2-4 hours.

[0018] More preferably, the mass ratio of the nanofiller to the bio-based organic acid is (1-3): (2-7).

[0019] The organic solvent is selected from dichloromethane.

[0020] The bio-based nanocomposite material used in the present invention can improve the internal molecular structure of asphalt at the microscopic level, increase its toughness and ductility, and reduce the risk of fatigue damage. The surface functionalization treatment of nanomaterials using bio-based organic acids can enhance the surface lipophilicity of nanofillers, promote the interaction between nanofillers and asphalt, and enhance the interfacial bonding performance, making it easier to disperse in the asphalt matrix, reducing aggregation and agglomeration, thereby improving the uniformity, stability and overall performance of high-viscosity asphalt. In addition, bio-based organic acids can also reduce the hydrophilicity of nanofillers, thereby enhancing the ability of asphalt materials to resist water erosion.

[0021] Preferably, the tackifier is C9 petroleum resin; the antioxidant is prepared by compounding UV 531, nano-TiO2, Irganox 1010 and Irgafos 168 in a mass ratio of 1:6:0.3:0.6.

[0022] Technical solution 2:

[0023] A method for preparing the above-mentioned bio-based compatible and stable particles comprises the following steps: weighing raw materials, uniformly mixing the heat-triggered bio-based cross-linking agent, bio-based nanocomposite material, tackifier, antioxidant and titanate coupling agent, injecting the obtained mixture into a twin-screw extruder, melt-mixing at 100-130°C for 3-6 minutes, extruding into filaments, pelletizing and drying to obtain the bio-based compatible and stable particles.

[0024] Technical solution three:

[0025] An application of the above-mentioned bio-based compatible stable particles in the preparation of modified high-viscosity asphalt.

[0026] Technical solution 4:

[0027] A bio-based compatible stable particle modified high-viscosity asphalt comprises the following raw materials, measured by weight: 90-100 parts of base asphalt, 7.5-10 parts of SBS and 15-20 parts of the above-mentioned bio-based compatible stable particles.

[0028] The special structure of the titanate coupling agent in the bio-based compatible stable particles enables it to combine with the polar part of the bio-based nanocomposite, SBS molecules and the non-polar part of the asphalt, thus forming a good interface bridge between the bio-based nanocomposite, SBS and asphalt. The titanate coupling agent can also effectively promote the combination of various phases by providing a larger contact area and chemical interactions such as hydrogen bonds and van der Waals forces, thereby reducing the risk of phase separation and aggregation and improving the overall performance of high-viscosity asphalt.

[0029] Technical solution five:

[0030] A method for preparing the above-mentioned bio-based compatible stable particle modified high-viscosity asphalt comprises the following steps: weighing raw materials, sequentially adding SBS and the above-mentioned bio-based compatible stable particles into matrix asphalt, and preparing the bio-based compatible stable particle modified high-viscosity asphalt through shearing, stirring and constant temperature development.

[0031] Preferably, the temperature of the isothermal development is 160-190°C.

[0032] Compared with the prior art, the present invention has the following advantages and technical effects:

[0033] The present invention uses heat-triggered bio-based cross-linking agents and bio-based nanocomposites to replace cross-linking agents such as sulfur and polyphosphoric acid commonly used in the prior art, and prepares them into bio-based compatible stable particles that can be directly used, which has obvious advantages of material stability and convenient construction. The application of bio-based materials can effectively reduce the emission of harmful gases during the production and application of high-viscosity asphalt and improve the construction environment. At the same time, the biodegradability of bio-based materials provides strong support for environmental protection and significantly reduces the long-term pollution risk after the use of materials.

[0034] The solid sealant effectively protects the reactivity of the -NCO end of the triggered bio-based cross-linker, facilitating practical operation and long-term storage; the high temperature environment (160℃-180℃) during the preparation of high-viscosity asphalt can successfully activate the reactivity of the triggered bio-based cross-linker, allowing it to participate in the chemical modification of high-viscosity asphalt in a timely manner, thereby forming a more developed and stable chemical cross-linking network structure.

[0035] The components in the bio-based compatible and stable particles provided by the present invention can produce a synergistic effect, jointly promoting the compatibility and stability enhancement and overall performance improvement of high-viscosity asphalt. The bio-based nanocomposite material can be evenly dispersed in the high-viscosity asphalt to form a more uniform and dense network structure, thereby improving the overall strength and toughness of the high-viscosity asphalt; the titanate coupling agent can serve as a "bridge" to establish an effective mutual connection between SBS, bio-based nanocomposite materials and asphalt, thereby improving the compatibility and stability of the high-viscosity asphalt system.

[0036] The present invention provides a bio-based compatible stable particle suitable for high-viscosity asphalt, and improves the overall performance of road engineering materials by introducing renewable materials, thereby providing a sustainable solution for environmentally friendly road construction. This not only conforms to the development trend of modern materials science, but also responds to the world's increasing environmental protection needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0038] Figure 1 A flow chart for preparing bio-based compatible stable particles provided by the present invention. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] In the embodiments of the present invention, “parts” refer to “parts by mass” unless otherwise specified.

[0045] Sources of raw materials in the embodiments and comparative examples of the present invention:

[0046] The base asphalt is Shell No. 70 asphalt produced by Zhenjiang Shell (China) Asphalt Co., Ltd.;

[0047] 4,4′-Diphenylmethane diisocyanate and dibutyltin dilaurate were purchased from Anhui Zesheng Technology Co., Ltd.;

[0048] Nano calcium carbonate was a colorless, odorless white powder purchased from Beijing Mairida Technology Co., Ltd.;

[0049] Oleic acid was purchased from Xilong Chemical Reagent Co., Ltd.;

[0050] Titanate coupling agent was provided by Hangzhou Jessica Chemical Co., Ltd.;

[0051] UV 531, nano-TiO2, Irganox 1010 and Irgafos 168 for the preparation of antioxidants were purchased from MacLean Biochemical Technology Co., Ltd.;

[0052] N,N-Dimethylacetamide, 3,5-dimethylpyrazole, aromatic oil, and polyphosphoric acid were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0053] Example 1 Preparation method of a heat-triggered bio-based cross-linking agent

[0054] S1: In a nitrogen atmosphere, 0.3 mol of 4,4'-diphenylmethane diisocyanate and 0.1 mol of epoxy castor oil were added into a three-necked flask in sequence, and two drops of dibutyltin dilaurate catalyst were added dropwise, and the resulting mixture was stirred and reacted at 50°C for 3 h;

[0055] S2: Dissolve 0.24 mol of 3,5-dimethylpyrazole in N,N-dimethylformamide solution, so that the ratio of -NCO group in 4,4'-diphenylmethane diisocyanate, -OH group in epoxy castor oil and -OH group in 3,5-dimethylpyrazole is 1:0.25:0.6, drop the obtained N,N-dimethylformamide solution into the reaction solution obtained in S1, and continue stirring the reaction for 3 hours;

[0056] S3: The product obtained in S3 was dried in a vacuum drying oven at 80° C. for 2 h to prepare a heat-triggered bio-based cross-linking agent.

[0057] Example 2 Preparation method of bio-based nanocomposite material

[0058] S1: Add 10g of nano calcium carbonate into 100mL of dichloromethane solution, mix well and preheat to 90°C, then add 20mL (21g) of oleic acid and 2g of triethylaminosilane, and stir to react for 2h;

[0059] S2: The reactants obtained in S1 are placed on a filter for filtration and separation, and washed with ethanol and distilled water in sequence. The products are vacuum dried at 80° C. for 3 h to prepare a bio-based nanocomposite material.

[0060] Example 3 A method for preparing bio-based compatible stable particles

[0061] S1: 3g of the heat-triggered bio-based cross-linking agent prepared in Example 1, 5g of the bio-based nanocomposite material prepared in Example 2, 3g of C9 petroleum resin, 1g of antioxidant (prepared by mixing UV 531, nano-TiO2, Irganox 1010 and Irgafos 168 in a mass ratio of 1:6:0.3:0.6), and 2g of titanate coupling agent were mixed uniformly in a mixer;

[0062] S2: The mixture obtained in S1 was injected into a twin-screw extruder, melt-mixed at 120°C for 4 minutes, and then extruded into filaments, pelletized, and dried to obtain bio-based compatible stable granules.

[0063] Figure 1 A flow chart for preparing bio-based compatible stable particles provided by the present invention.

[0064] Example 4-6 Preparation method of bio-based compatible stable particle modified high-viscosity asphalt

[0065] Table 1

[0066] Material Example 4 Example 5 Example 6 Base asphalt(g) 100 95 90 SBS(g) 10 8 7.5 Bio-based compatible stable particles (g) 15 18 20

[0067] S1: Weigh each raw material according to the mass fraction in Table 1.

[0068] S2: Heat the base asphalt at 180°C to a molten state, then add SBS in small amounts and multiple times, and use a mechanical shearing machine to shear the mixture at a shear rate of 2000r / min for 20min;

[0069] S3: adding the bio-based compatible stable particles prepared in Example 3 to the mixture, and increasing the shear rate to 5000 r / min and continuing shearing for 1 h;

[0070] S4: The mixture obtained in S3 was transferred to a mechanical stirrer and stirred at a speed of 700 r / min for 30 minutes;

[0071] S5: The mixture obtained in S4 is placed in an oven at 170°C for 30 minutes to obtain a bio-based compatible stable particle modified high-viscosity asphalt.

[0072] Comparative Example 1

[0073] S1: 100g of base asphalt was heated to a molten state at 180°C, 5g of aromatic oil was added, and then 7.5g of SBS was added in small amounts and several times, and the mixture was sheared at a shear rate of 2000r / min for 20min using a mechanical shearing machine;

[0074] S2: Add 0.75 g of polyphosphoric acid (PPA) to the mixture obtained in S1 and increase the shear rate to 5000 r / min and continue shearing for 1 h;

[0075] S3: The mixture obtained in S2 was transferred to a mechanical stirrer and stirred at a speed of 700 r / min for 30 minutes;

[0076] S4: Place the mixture in an oven at 170°C for 30 minutes to obtain modified high-viscosity asphalt.

[0077] Comparative Example 2

[0078] The same as Example 4, except that no heat-triggered bio-based cross-linking agent is added to the bio-based compatible stable particles prepared in Example 3.

[0079] Comparative Example 3

[0080] The same as Example 4, except that no bio-based nanocomposite material is added to the bio-based compatible and stable particles prepared in Example 3.

[0081] Comparative Example 4

[0082] The same as Example 4, except that no titanate coupling agent is added to the bio-based compatible stable particles prepared in Example 3.

[0083] Performance test

[0084] Compatibility stability test:

[0085] According to the Technical Specifications for Highway Asphalt Pavement Construction (JTG F40-2004), standard segregation experiments were carried out on the high-viscosity asphalt materials prepared in Examples 4-6 and Comparative Examples 1-4. The softening point difference of the asphalt in the upper and lower parts of the aluminum foil tube was tested after the asphalt samples were vertically stored in an oven at 163°C for 48 hours. The test results are shown in Table 2.

[0086] Table 2

[0087]

[0088] It can be seen from the test data in Table 2 that the conventional method of adding light oil and polyphosphoric acid in Comparative Example 1 cannot make the softening point difference of high-viscosity asphalt reach the standard requirement of less than 2.5°C, while the bio-based compatible and stable particles proposed in the present invention can effectively improve the compatibility and stability of high-viscosity asphalt. Comparing the softening point difference values ​​of Examples 4-6 with Comparative Examples 1-4, it is confirmed that the synergistic effect of the components in the bio-based compatible and stable particles provided by the present invention can effectively improve the compatibility and stability of high-viscosity asphalt.

[0089] Road performance test:

[0090] In order to study the effect of the bio-based compatible stable particles prepared by the present invention on the high-temperature performance of high-viscosity asphalt, the present invention carried out a multiple creep recovery (MSCR) test at 64°C and a zero shear viscosity (ZSV) test at 60°C by using a DSR instrument according to the ASTMD 7175 (AASHTOT 31509) specification; a linear amplitude sweep (LAS) test was performed according to the AASHTO TP 101 specification to test the fatigue life times of the high-viscosity asphalt prepared in Examples 4-6 and Comparative Examples 1-4 under 20°C and 2.5% strain conditions. The test results are shown in Table 3. Among them, the elastic recovery rate refers to the degree of rebound of the material after the pressure is released after being subjected to a certain pressure at a certain temperature. It reflects the recovery ability of the material after being subjected to force; shear viscosity (ZSV) is an important indicator for evaluating the fluidity and stability of asphalt under long-term load. A higher ZSV indicates that the asphalt has stronger resistance to deformation; the fatigue life calculated based on the LAS experiment is a key indicator for evaluating the performance of asphalt under repeated loads. A higher fatigue life indicates that the asphalt material has superior durability and crack resistance under dynamic loading conditions, indicating that it can better maintain structural integrity and performance in practical applications.

[0091] Table 3

[0092]

[0093] It can be seen from Comparative Table 3 that compared with the modified high-viscosity asphalt of Comparative Example 1 in which light oil and polyphosphoric acid are added by the traditional method, the high-temperature rheological properties and fatigue resistance of the high-viscosity asphalt can be effectively improved by adding the bio-based compatible stable particles prepared by Examples 4-6 of the present invention. It can be seen from the experimental data obtained from Comparative Examples 1-4 that the synergistic effect of the components in the bio-based compatible stable particles provided by the present invention can effectively improve the high-temperature rheological properties and fatigue resistance of the high-viscosity asphalt.

[0094] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A bio-based compatible stable particle, characterized in that: The raw materials include a heat-triggered bio-based cross-linking agent, a bio-based nanocomposite material, a tackifier, a titanate coupling agent and an antioxidant.

2. The bio-based compatible stable particles according to claim 1, characterized in that: The mass ratio of the heat-triggered bio-based cross-linking agent, the bio-based nano-composite material, the tackifier, the titanate coupling agent and the antioxidant is (3-5):(3-6):(3-5):(2-4):

1.

3. The bio-based compatible stable particles according to claim 2, characterized in that: The raw materials of the heat-triggered bio-based cross-linking agent include polyisocyanate compounds, bio-based polyols, dibutyltin dilaurate and a solid blocking agent.

4. The bio-based compatible stable particles according to claim 3, characterized in that: The preparation method of the heat-triggered bio-based cross-linking agent comprises the following steps: under a nitrogen atmosphere, dripping the dibutyltin dilaurate into a mixture of the polyisocyanate compound and the bio-based polyol, heating and stirring to react, then dripping a solution containing a solid blocking agent, continuing to stir and react, and vacuum drying the reaction product to obtain the heat-triggered bio-based cross-linking agent.

5. The bio-based compatible stable particles according to claim 1, characterized in that: The raw materials of the bio-based nano-composite material include nano-fillers, bio-based organic acids and catalysts.

6. The bio-based compatible stable particles according to claim 5, characterized in that: The preparation method of the bio-based nano-composite material comprises the following steps: adding the nano-filler into an organic solvent, mixing and preheating, then adding the bio-based organic acid and a catalyst, stirring for reaction, filtering, washing, and vacuum drying to prepare the bio-based nano-composite material.

7. A method for preparing the bio-based compatible stable particles according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: weighing raw materials, uniformly mixing the heat-triggered bio-based cross-linking agent, the bio-based nanocomposite material, the tackifier, the antioxidant and the titanate coupling agent, injecting the obtained mixture into a twin-screw extruder, melt-mixing for 3-6 minutes at 100-130° C., extruding into filaments, pelletizing and drying to prepare the bio-based compatible stable particles.

8. Use of the bio-based compatible stable particles according to any one of claims 1 to 6 in the preparation of modified high-viscosity asphalt.

9. A bio-based compatible stable particle modified high-viscosity asphalt, characterized in that: The raw materials are as follows, calculated by weight: 90-100 parts of base asphalt, 7.5-10 parts of SBS and 15-20 parts of the bio-based compatible stable particles according to any one of claims 1-6.

10. A method for preparing the bio-based compatible stable particle modified high-viscosity asphalt according to claim 9, characterized in that: The method comprises the following steps: weighing raw materials, sequentially adding SBS and the bio-based compatible stable particles described in any one of claims 1 to 6 into matrix asphalt, and preparing the bio-based compatible stable particle modified high-viscosity asphalt through shearing, stirring and constant temperature development.

Citation Information

Patent Citations

  • Polymer modified asphalt stabilizer and preparation method thereof

    CN102977619A

  • SBS modified asphalt stabilizer, SBS modified asphalt and preparation process of SBS modified asphalt

    CN118185328A

  • Vegetable-oil-based polyurethane modified asphalt and mixture containing vegetable-oil-based polyurethane modified asphalt

    CN106317915A

  • Roofing polyurethane modified asphalt waterproof paint and preparation method thereof

    CN108047953A

  • High-viscosity modified asphalt based on SBS / polyurethane compounding and preparation method thereof

    CN109553991A